Identification and Characterization of the Bioactive Polyphenols and Volatile Compounds in Sea Buckthorn Leaves Tea Together With Antioxidant and α-Glucosidase Inhibitory Activities - Wang, Ningning; Wen, Xiufeng; Gao, Yan; Lu, Shunguang; Li, Yimeng; Shi, Yanbin; Yang, Zhigang (Frontiers in Nutrition, 2022)
Sea buckthorn leaves have been used for tea making in food field gradually. This study was carried out to characterize the bioactive polyphenols and volatile compounds in sea buckthorn leaves (SL), sea buckthorn leaves green tea (SGT), and sea buckthorn leaves black tea (SBT) by using high-performance liquid chromatography with an UV detector (HPLC-UV), the liquid chromatography-mass spectrometry (LC-MS), and headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS), in combination with multivariate analysis. A total of 48 non-volatile metabolites and 295 volatile metabolites were identified. Then, the total polyphenol and total flavonoid contents in SL, SGT, and SBT were also analyzed. Moreover, SL and SGT showed greater antioxidant activities based on 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS), and oxygen radical absorbance capacity (ORAC) results. At the concentration of 0.1 mg/ml, their DPPH and ABTS radical scavenging ratios were 66 to 95%, while SBT exhibited lower antioxidant activity of 26 to 44%. SL, SGT, and SBT displayed moderate α-glucosidase inhibitory activity.